Case studies to illustrate the rotorcraft certification by simulation process; CS 29/27 dynamic stability requirements - Lu, Linghai; Padfield, Gareth D.; White, Mark D.; Dadswell, Christopher; Quaranta, Giuseppe; van’t Hoff, Stefan; Podzus, Philipp (German Society for Aeronautics and Astronautics (DGLR: Deutsche Gesellschaft für Luft- und Raumfahrt), 2023)
This paper is one of a set presented at the 49th European Rotorcraft Forum displaying results from the EU Clean Sky 2 project, Rotorcraft Certification by Simulation (RoCS). The process developed by the RoCS team provides guidance on the requirements for the use of simulation in certification and features four case studies that illustrate aspects of the process applied using flight simulation models and flight test data provided by Leonardo Helicopters. This paper presents the case study on Dynamic Stability, for the relevant certification paragraphs in the EASA Certification Specifications CS-27 and CS-29. The Dynamic Stability paragraphs from the Specifications are described and results from simulation model fidelity assessment, and updating compared with test data, are presented for a reference flight condition. The credibility of extrapolations of the flight simulation model results to conditions at higher altitude, different airspeeds and vertical rates of climb are then discussed. Preliminary results from piloted simulation trials, with a ‘new’ flight test manoeuvre, are included to illustrate flight simulator fidelity assessment methods and to explore the veracity of the stability margins set by the Certification Specifications.
© The Authors